ANALISIS HUBUNGAN ANTARA KELANDAIAN JALAN DAN PANJANG LANDAI KRITIS TERHADAP KESELAMATAN LALU LINTAS (STUDI KASUS: RUAS JALAN SETIABUDI SEMARANG DARI KM 8+100 SAMPAI KM 9+350) - Syafiiq Muhammad Ridlo; izazulfina izazulfina; Ismiyati Ismiyati; Amelia Kusuma Insriastuti (Jurnal Karya Teknik Sipil, 2013)
Setiabudi street, Semarang, is access road to the southern area of Semarang, that is often used in addition to highway. This road connects the Semarang to Tembalang and Banyumanik, also connect to the southern area of Central Java. Some segments have gradient road more than 8% and critical gradient oad is different with RSNI Geometrik Jalan Perkotaan 2004. Setiabudi street that have gradient road > 8% cause acceleration of the vehicle decrease. It also causes traffic accident. Based on the issues conducted research to review the relationships of gradient road and critical gradient length to road safety. The survey method use spot speed and traffic counting. Secondary data is geometric of the Setiabudi street, traffic accident and annual daily traffic. Analytical methods to determine the relationship between gradient road and critical gradient road use regression method and descriptive analysis. The relationship of gradient road and critical gradient length to road safety is indicated by polynomial regression model Y = 174 222 - 3.827E-013X - 13166.052X2 + 3.995E-011X3 (R square= 0.998). The correlation value indicate the relationship gradient road and road safety is close. Some segments with gradient road and critical gradient length is high not necessarily cause a high number of accidents. The simulation results can be concluded the reduction of the degree of saturation cause risk of accident is reduced.